2015
DOI: 10.1098/rsfs.2015.0020
|View full text |Cite
|
Sign up to set email alerts
|

Tiny bubbles challenge giant turbines: Three Gorges puzzle

Abstract: Since the birth of the first prototype of the modern reaction turbine, cavitation as conjectured by Euler in 1754 always presents as a challenge. Following his theory, the evolution of modern reaction (Francis and Kaplan) turbines has been completed by adding the final piece of the element ‘draft-tube’ that enables turbines to explore water energy at efficiencies of almost 100%. However, during the last two and a half centuries, with increasing unit capacity and specific speed, the problem of cavitation has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
(101 reference statements)
0
20
0
Order By: Relevance
“…The specific motivation of the study reported herein is the phenomenon of incipient cavitation in turbulent liquid flows, which is a macroscopic consequence of pressure fluctuations on microscopic bubbles (or nuclei) present in the liquid 5,6 . Though the dynamics of cavitation bubbles has been well established following the pioneering work of Plesset 7 , accurate prediction of cavitation inception in technologically relevant flows remains a challenge 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The specific motivation of the study reported herein is the phenomenon of incipient cavitation in turbulent liquid flows, which is a macroscopic consequence of pressure fluctuations on microscopic bubbles (or nuclei) present in the liquid 5,6 . Though the dynamics of cavitation bubbles has been well established following the pioneering work of Plesset 7 , accurate prediction of cavitation inception in technologically relevant flows remains a challenge 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, a serious damage was observed on the guide plate soon after the commissioning, accompanied by severe pressure fluctuations and machine vibrations. 22 In our previous work, 21,22 we found that the guide plate could possibly serve as a particular origin for the generations of the flow perturbations, which further interacts with the draft-tube surges. Our previous studies 23,24 also found that the guide plate increases the free-stream turbulence and adversely affects the flow field, particularly at the part load.…”
Section: Introductionmentioning
confidence: 89%
“…Introduction of the guide plate Figure 1 shows the comparison of the locations of spiral casing between cases with and without the guide plate (highlighted by the two red solid lines). 21 In Figure 1, R original is the radius of the spiral casing without the guide plate and R guide-plate is the radius of the spiral casing with the guide plate. It is notable that the unit size can be largely reduced by moving the spiral casing inwards while keeping the position of the butterfly edge of the stay ring as it used to be.…”
Section: Geometry and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Li [2] reveals a very strange erosion occurring on the giant turbines installed at the Three Gorges project that puzzles professionals. A hypothesis is proposed to illustrate this unknown cavitation-inception process.…”
mentioning
confidence: 99%